A Narrative Inquiry into Pre-Service English Teachers' Imagined Identities - Sarasa, María Cristina (GIST – Education and Learning Research Journal, 2016)
This paper explores co-construction processes of EIL (English as an international language) pre-service teacher identity in an undergraduate English Teacher Education Program at an Argentinean state university. The study focuses on the professional nature of future language teachers’ identities expressed in the individual stories the young people co-composed with the author working as participant researcher. The design employed narrative inquiry as a research methodology whose techniques allow the gathering of field texts inside and outside the Program’s classrooms. The overall study included 24 sophomores whose professional identities were conceptualized narratively during the 18-month-long inquiry. This paper offers four participants’ accounts, evincing the co-authoring of an imagined (future) teacher identity. After rendering the students’ stories, we briefly discuss some implications this power of envisioning the (prospective) teaching self may have for EIL teacher education